The Small Antigen of Hepatitis Delta Virus Interacts In-vivo with HuR - Ana Casaca; Celso Cunha (Research Perspectives of Microbiology and Biotechnology Vol. 5, 2024)
Hepatitis delta virus (HDV) was discovered in 1977 by Italian gastroenterologist Mario Rizzetto. The small and large delta antigens (S-HDAg and L-HDAg, respectively) represent two forms of the only protein encoded by the hepatitis Delta virus (HDV) RNA genome. Consequently, HDV relies, to a large extent, on the host cell machinery for replication and transcription. Using different approaches few cellular proteins were identified as S- HDAg or L-HDAg partners with limited evidence of their involvement in the modulation of the virus life cycle and mechanisms of pathogenesis. Here we performed a yeast two-hybrid screening of a human liver cDNA library to identify cellular proteins that bind to S-HDAg. We were able to identify HuR, a ubiquitously expressed protein involved in the regulation of gene expression at the posttranscriptional level, and associated with cancer, as an S-HDAg partner both in vitro and in vivo. HuR was found to be overexpressed and colocalized with HDAg in human hepatoma cells. siRNA knockdown of HuR mRNA resulted in inhibition of S-HDAg and L-HDAg expression. The obtained results suggest that HuR may play an important role in the HDV replication cycle and pathogenesis.